Framework for evaluating suitability of graphical user authentication for mobile banking - Kingsley Ugochukwu, Ejike Ekeke (2016)
User Authentication is a vital component in any Information System. There are various ways of implementing user authentication from using text-based passwords, biometric passwords and graphical images password. The importance of selecting an environment appropriate user authentication method is one of the crucial decisions in encouraging the user to adopt the application. The main purpose of User Authentication in applications is to allow the application to verify the identity of the person who wants to connect to the application being used. In mobile banking, research shows that the current mode of user authentication plays an important role in influencing customer’s intentions to use mobile banking services. The research problem stems out of the perceived low adoption of mobile banking. Further research revealed that the main problems for the low adoption of mobile banking includes the cognitive burden users’ face in remembering text-based passwords, the usability issues hindering the adoptability of mobile banking based on current mobile banking user authentication methods and the current mode of user authentication. One of the motivation for this research study stems out of the positive supporting research surrounding graphical user authentication as a viable alternative to text-based passwords. Tackling the adoption issues relating to mobile banking, a preliminary study done revealed that usability issues are one of the reasons that contribute to users’ hesitation to adopt mobile banking. Research done on the current models, methods and frameworks surrounding mobile banking usability revealed that most of the studies done focused on usability issues, security issues, authentication issues but we were unable to find any that were based on the suitability of the authentication model chosen. Hence the limitation of the current models was a non-holistic framework targeted at the developer to evaluate the suitability/usability of the user authentication framework for mobile banking. The main objective of this research study is to propose a framework for evaluating graphical user authentication suitability for mobile banking. This study approached the problem from a holistic view of mobile banking. In order to achieve this objective, an analysis of the characteristics, quality factors and the factors affecting suitability and adoptability in mobile banking was done. In this research study, literature review was conducted on the areas critical and surrounding Mobile Banking and Graphical User Authentication. A solution was built and the framework was used to evaluate the graphical user authentication chosen. Results were statistically analyzed and discussed. The framework was evaluated against evaluation components such as Accuracy, Response Time, Password Memorability and Simplicity and an expert review was done to validate the framework. In choosing the proposed framework, a survey done showed that 75% of the respondents were open to the solution. For testing the prototype development, respondents were asked to choose their graphical password by choosing 3 points on the image as their password. Each graphical image password had hotspots which were blocked off during authentication. A total 50 respondents were asked to use the solution. Results from this study showed that all factors and relationships in the framework suggest a positive and high correlative significance between them. Simplicity as an evaluation component is very vital in the framework as it showed a significant relationship between Content and Convenience as well as Accuracy and Response Time. In conclusion, this proposed framework serves as a guiding tool for evaluating the suitability of graphical user authentications for mobile banking user authentication.